Low back pain: a call for action. Issue 10137 (9th June 2018) - Buchbinder, Rachelle; van Tulder, Maurits; Öberg, Birgitta; Costa, Lucíola Menezes; Woolf, Anthony; Schoene, Mark; Croft, Peter; ,
Summary: Low back pain is the leading worldwide cause of years lost to disability and its burden is growing alongside the increasing and ageing population. 1 Because these population shifts are more rapid in low-income and middle-income countries, where adequate resources to address the problem might not exist, the effects will probably be more extreme in these regions. Most low back pain is unrelated to specific identifiable spinal abnormalities, and our Viewpoint, the third paper in this Lancet Series, 2, 3 is a call for action on this global problem of low back pain.